US-Pakistan cooperation and Pakistan's security post 9/11 - Tamana, Aazar (Curtin University, 2010)
The thesis addresses the implications of US-Pakistan cooperation post 9/11 for Pakistan’s security. The terrorist attacks of 9/11 on World Trade Center and Pentagon necessitated US-Pakistan cooperation to combat terrorism, which had mixed consequences for Pakistan’s security. At the domestic level, on the one hand, US-Pakistan collaboration helped strengthen the wide consensus in Pakistani society opposed to terrorism. Further, the US encouraged and supported Pakistan’s transition to democracy in 2007-2008. On the other hand, political violence grew in Pakistan, in part due to Pakistan’s close alliance with the US, especially in Federally Administered Tribal Areas (FATA) and Balochistan which eroded Pakistan’s domestic security. At the regional level, US-Pakistan cooperation post 9/11 enhanced Pakistan’s security in two significant ways. First, during India-Pakistan military standoff in 2001/2002, the US played a vital role in averting a war between the two adversaries. Second, the US encouraged composite dialogue between India and Pakistan that played a major role in ensuring peace between the two hostile states post 9/11.